Perancangan dan Evaluasi NUMORi sebagai Media Pembelajaran Numerasi Montessori Berbasis Cetak 3D untuk Anak Usia Dini - Verdian, Ihsan; Primadasa, Yogi (Fakultas Komputer - Universitas Universal, 2025)
The long-term objective of this research is to develop an applied scientific design model in the field of multimedia engineering for producing 3D-based educational products aligned with the Montessori learning philosophy. This study aims to contribute to the establishment of a standardized design framework for early childhood numeracy learning media that integrates scientific rigor, aesthetic value, and functional effectiveness. The specific target of this research is the development of a physical prototype called NUMORi (Numerical Montessori 3D Model), an interactive learning aid produced using 3D printing technology and designed through a scientific design approach, along with the acquisition of intellectual property rights (IPR) for the educational product and the development of an implementation guidebook for kindergarten learning environments. The research employs a scientific design methodology consisting of needs observation, design problem formulation, 3D model design hypothesis development, experimentation through modeling and 3D printing, and evaluation through trials in Montessori schools in Batam City. Data are collected through observations, teacher interviews, and expert assessments. The findings are expected to provide both theoretical and practical contributions to the development of scientific design methods in interactive multimedia and education.